The view from afar - Claude Lévi-Strausse (Univ. of Chicago Press, 1992)
The book touches on the major themes: kindship, social organization, mythology, ritual, art. It is divided into 5 parts: the Innate and the acquired; Family, marriage, kindship; the Environment and its representation; Beliefs, myths, and rites; Constraint anf freedom